Information Theoretic Security 6th International Conference, ICITS 2012, Montreal, QC, Canada, August 15-17, 2012. Proceedings - Smith, Adam.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the proceedings of the 6th International Conference on Information Theoretic Security, ICITS 2012, held in Montreal, Canada, in August 2012. The 11 full papers presented in this volume were carefully reviewed and selected from 46 submissions. In addition 11 papers were selected for the workshop track, abstracts of 7 of these contributions are also included in this book. Topics of interest are: physical layer security; multiparty computations; codes, lattices and cryptography; authentication codes; randomness extraction; cryptography from noisy channels; wiretap channels; bounded-storage models; information-theoretic reductions; quantum cryptography; quantum information theory; nonlocality and nonsignaling; key and message rates; secret sharing; physical models and assumptions; network coding security; adversarial channel models; information-theoretic tools in computational settings; implementation challenges; and biometric security.
Keywords: Computer science; Data protection; Data encryption (Computer science).; Coding theory; Information Systems; Computer Science; Systems and Data Security; Data Encryption; Coding and Information Theory; e-Commerce/e-business.; Management of Computing and Information Systems; Computers and Society